Locating fault on transmission line with static var compensator based on phasor measurement unit - Ngô Minh Khoa; Đoàn Đức Tùng (My University, 2018)
Locating fault on transmission line with static var compensator based on phasor measurement unit
Keywords: Định vị sự cố; Static Var Compensator; PMU